Review article: Clinical characteristics and outcomes of patient presentations to the emergency department via police: A scoping review. (21st May 2019) - Crilly, Julia; Johnston, Amy NB; Wallis, Marianne; Polong‐Brown, Josea; Heffernan, Ed; Fitzgerald, Gerard; Young, Jesse T; Kinner, Stuart
Abstract: People brought in by police (BIBP) to the ED are a potentially vulnerable group. This narrative scoping review aimed to identify, evaluate and summarise current literature regarding the frequency of presentation, demographic and clinical profile of patients (including reason for presentation), care delivery, and outcomes for people BIBP to the ED, and identify current gaps in knowledge. The review involved searching EMBASE, CINAHL and PubMed using a combination of terms: emergency/ED coupled with police custody/watch house or police presentation, for papers published in English language from January 2006 to November 2017. A total of 20 studies met the inclusion criteria. These included 17 observational (non‐randomised controlled trials) quantitative studies and three descriptive case reports. The proportion of presentations to ED that were BIBP varied depending on the study design and sampling frame. People BIBP often presented with mental health problems, substance use problems, aggressive behaviour and injury caused by self or others. Of studies focused specifically on patients arriving to the ED in mental health crisis (i.e. suicidal ideation or self‐harm), 18–27% were BIBP. ED presentations BIBP were mostly male and typically younger than people arriving by other means. The nature of care provided in the ED and outcomes of the acute episode of care were typically not well described. Limited research regarding people BIBP to the ED limits the ability to comprehensively understand their demographic and clinical profile and outcomes of emergency care. Further research is required to inform if and where in the patient's journey further improvements may be targeted.